Afrotropics on the wing: phylogenomics and historical biogeography of awl and policeman skippers. (19th October 2020) - Toussaint, Emmanuel F.A.; Chiba, Hideyuki; Yago, Masaya; Dexter, Kelly M.; Warren, Andrew D.; Storer, Caroline; Lohman, David J.; Kawahara, Akito Y.
Abstract: The Old‐World Tropics encompass many unique biomes and associated biotas shaped by drastic climate and geological changes throughout the Cenozoic. Disjunct distributions of clades between the Afrotropics and the Oriental regions are testament to these changes. Awl and policeman skippers (Hesperiidae: Coeliadinae) are disjunctly distributed with some genera endemic to the Afrotropics and others restricted to the Oriental and Australian regions. We reconstruct the phylogeny of these butterflies using target exon capture phylogenomics. We also generate a dated framework for this clade that uses the putatively oldest known butterfly fossil to estimate the historical biogeography of Coeliadinae using a model‐based approach. We infer a stable and robust phylogeny for the subfamily, with all but one Afrotropical lineage forming a derived clade. The African genus Pyrrhiades syn. nov. is placed in synonymy with Coeliades to accommodate the new phylogeny. Our comparative dating exercise casts doubt on the assignment of the fossil Protocoeliades kristenseni as a derived Coeliadinae and suggests, along with our biogeographic estimation, a split of Coeliadinae from the rest of skippers in the Palaeocene ca . 70 million years ago. The origin of crown Coeliadinae skippers is estimated in Indomalaya during the late Eocene ca . 36 million years ago, with subsequent Oligocene colonisation events toward the Australian region and the Afrotropics. Colonisation of the Afrotropics from the Indian region occurred during climatic transition, associated biome shifts, and the closure of the Tethys Ocean, which likely allowed geodispersal through the Arabian Peninsula. The current disjunct distribution of Coeliadinae in the Old World Tropics may result from the emergence of savannahs in the Miocene that progressively replaced woodlands and forests in the Arabian Peninsula and western Asia. Coeliadinae skippers are almost exclusively dicot feeders and were likely extirpated as grasslands became dominant, resulting in the present‐day disjunct distribution of these butterflies. Abstract : First comprehensive dated phylogenomic tree of Coeliadinae butterflies Modern Coeliadinae originated in Indomalaya in the Eocene and colonised the Afrotropics after the closure of the Tethys Ocean Current disjunct distribution of Coeliadinae may result from the emergence of savannahs in the Miocene